2015
DOI: 10.1371/journal.pone.0135683
|View full text |Cite
|
Sign up to set email alerts
|

Positive Association between APOA5 rs662799 Polymorphism and Coronary Heart Disease: A Case-Control Study and Meta-Analysis

Abstract: ObjectiveApolipoprotein A5 (APOA5) is associated with plasma triglyceride (TG) levels, a risk factor for coronary heart disease (CHD). This study explored the association between CHD and the APOA5 rs662799 polymorphism.MethodsWe collected 1,521 samples (783 CHD patients and 738 controls) for this case-control study. Meta-analysis was performed using Review Manager Software and Stata Software.ResultsSignificant differences were observed between CHD cases and controls at the level of both genotype (χ2 = 8.964, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 65 publications
2
22
0
Order By: Relevance
“…In the literature, some studies demonstrated that this polymorphism is associated with higher levels of TG [ 12 25 ], total cholesterol (TC) [ 17 ] and LDL-C [ 18 ], and lower levels of HDL-C [ 14 22 ]. A significant association between this variant and the presence of CHD was also reported in several studies [ 22 24 , 26 , 27 ]. However, whether this polymorphism is associated with the severity of CHD has not been reported before.…”
Section: Introductionsupporting
confidence: 73%
“…In the literature, some studies demonstrated that this polymorphism is associated with higher levels of TG [ 12 25 ], total cholesterol (TC) [ 17 ] and LDL-C [ 18 ], and lower levels of HDL-C [ 14 22 ]. A significant association between this variant and the presence of CHD was also reported in several studies [ 22 24 , 26 , 27 ]. However, whether this polymorphism is associated with the severity of CHD has not been reported before.…”
Section: Introductionsupporting
confidence: 73%
“…A number of SNPs of APOA5 associated with TG and HDL-C levels have been reported [9]. Among these SNPs, rs662799, which is located in the promotor region of the APOA5 gene, was associated with TG levels and coronary heart disease in a Japanese and a Chinese population [10,11]. Association between rs662799 and elevated TG level was validated in Koreans [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…Its polymorphism has been found to be involved in the development of diabetic microangiopathy. 21,40 Sex differences in the HIF1A polymorphism have also been demonstrated by Gu et al, 40 who studied patients with diabetic nephropathy. These authors showed that a particular genetic variant of HIF1A decreases the risk of diabetic nephropathy in men, but not in women.…”
Section: Supplementary Materialsmentioning
confidence: 55%